In-vitro Gd-DTPA Relaxometry Studies in Oxygenated Venous Human Blood and Aqueous Solution at 3 and 7T - Kalavagunta, Chaitanya (2014)
In-vitro T(1) and T(2)(*) relaxivities (r(1) and r(2)(*)) of Gd-DTPA (GaD) in oxygenated human venous blood (OVB) and aqueous solution (AS) at 3T and 7T were calculated. GaD concentrations ([GaD]) in OVB and AS were prepared in the range 0–5 mM. All measurements were acquired at 37±2 °C. At both 3T and 7T, a linear relationship was observed between [GaD] and R(1) in both AS and OVB. At 7T, r(1) in AS decreased by 7.5% (p = 0.045) while there was a negligible change in OVB. With respect to R(2)(*), a linear relationship with [GaD] was only observed in AS, while a more complex relationship was observed in OVB; quadratic below and linear above 2 mM at both field strengths. There was a significant increase of over four-fold in r(2)(*) with GaD in OVB at 7T (for [GaD] above 2mM, p ≪0.01) as compared to 3T. Furthermore, in comparison to r(1), r(2)(*) in AS was less than two-fold higher at both field strengths while in OVB it was ~twenty-fold and ~ninety-fold higher at 3T and 7T, respectively. This observation emphasizes the importance of r(2)(*) knowledge at high magnetic fields, ≥3T. The comparison between r(1) and r(2)(*) presented in this work is crucial in the design and optimization of high field MRI studies making use of paramagnetic contrast agents. This is especially true in multiple compartment systems such as blood where r(2)(*) dramatically increases while r(1) remains relatively constant with increasing magnetic field strength.